ANALISIS KEBIJAKAN KAMPUS MERDEKA TENTANG TEKNIS IMPLEMENTASI HAK BELAJAR MAHASISWA 3 SEMESTER DI LUAR PROGRAM STUDI - Indah Lestari Hasibuan (Raudhah - Proud To Be Professional, 2023)
Abstract This paper intends to reveal the object of the many actions after graduating from tertiary institutions, and reveal how many tertiary institutions have or have not implemented this independent campus policy. With the policy regarding an independent campus, one of the programs namely the right to study for three semesters outside the study program, this really helps students to equip themselves so they are ready to enter the world of work. The type of research used is qualitative research. The method used in this research is library research (Library Study) with a critical approach to understanding problems in the world of higher education. The stages carried out in this study were: First, collecting information from data sources such as books, journals, and news about research, second, reading the information obtained, third, analyzing the information obtained, fifth, concluding the results of the analysis obtained. The results of the analysis of the data obtained are problems regarding college graduates which can be said to be difficult to get a job right away. Therefore, because of this there are causes, including: the uneven implementation of the independent campus policy due to the many obstacles faced by both lecturers and students. In this article, we have answered how the implementation and impact of the three-semester study rights program outside of this study program starts with what are the technical obstacles in implementing one-on-one programs.